Pengaruh Kepelbagaian Kemahiran (Multi-Skilling) Terhadap Prestasi Kerja Kakitangan Sokongan Kementerian Pertahanan - Hisham Azlin, Zainun (2013)
The launch of Government Transformation Program (GTP) is a starting point towards a mind change of the whole people in the country. The changes brought about by the Government covering various aspects including human capital development. Talking about human capital, we cannot run away from discussing labor issues in the country, including those in the public sector. The need to improve self-competence as well as having a competitive advantage always been emphasized especially in the aspect of skills. Therefore, this study aims to examine the relationship and influence of various skills (multi-skilling) on the work performance of support staff working in the Ministry of Defence. This study is also aim to determine the strength on the influence of multiskilling elements such as supervision, leadership, self-regulation and multi-tasking with job performance. A total of 304 respondents were involved in this survey. Descriptive analysis techniques used to assess the level of performance and multi-skilling based on the demographic factors like educational level, gender and age. Whereas inferential analysis such as one way ANOVA, Post Hoc test, Pearson correlation and Standard Multiple Regression was used to test hypotheses formulated. The results showed that there are differences between the performance of multi-skilling and work performance based on the factors like length of service period, educational level and gender except for an age. In addition, there is also a significant relationship between the dimensions of multi-skilling (vertical and horizontal) on the work performance. The study also found that multi-skilling influenced work performance by 40.4% where multi-tasking is the best determinant followed by self-leadership and self-supervision. Meanwhile, the self regulatory element showed no significant effects on the work performance of the Ministry of Defence support staff